Pathogenıcıty Beauveria Bassiana (Deuteromycetes), Whıch Provıded By Addıtıonal Chıtın From Sources Tenebrio Molitor And Shrımp Skın On The Reproductıon Medıa Hypothenemus Hampei Ferrari. (Coleoptera: Scolytıdae) - Abdul Rizal AZ; Muhamad Rizki Miharja; Siwi Hardiastuti EK (Cita Konsultindo Research Center, 2023)
Beauveria bassiana is one of the biological agents to control insect pests, including the coffee berry borer. Adding chitin nutrition to the propagation media is essential to improve the quality of the spores and their pathogenicity. The research objective was to determine the effect of adding chitin from sources of Tenebrio molitor and shrimp shells with different concentrations in the propagation media on the spore quality and pathogenicity of beauveria bassiana. The research was conducted at the Protection Laboratory at the National Veterans Development University, Yogyakarta, from November 2022 to February 2023. The study used a completely randomized design as a treatment using multiplication media. beauveria bassiana without adding chitin (C0), media with chitin T. molitor 1 g/200 g (C1); Get it T. molitor 2 g/200 g (C2); Kitten T. molitor 3g/200g (C3); Shrimp shell chitin 3 g/200 g (C4); Shrimp shell chitin four g/200 g(C5); Shrimp shell chitin 5 g/200 g(C6). The treatment was repeated four times. The results showed that spore quality test, T. molitor chitin treatment 2 g/200 g (spore density 7.53x108 spores/mL and viability 84.48%) and shrimp shell chitin 4 g/200 g (spore density 7.34x108 spores) /mL and viability 83.09%) resulted in high-quality mushrooms. While the pathogenicity test, the treatment of T. Molitor chitin 2 g/200 g and shrimp shell 4 g/200 g produced good pathogenicity (the highest percentage of mortality; the fastest death rates were 5.1 and 4.7 days; the most secured 50% Lethal Time was 4.264 and 3.883 days and the lowest eating power of 0.55 and 0.51 grams.